Tailgut Cyst in a Child: A Case Report and Review of Literature - Ramendra Shukla; Jay Divyesh Patel; Sudhir B. Chandna; Urvish Parikh (Wolters Kluwer Medknow Publications, 2024)
Tailgut cysts are rare congenital abnormalities that develop due to failure of embryologic tailgut to involute. This generally manifests as a presacral, retrorectal and multicystic mass. It has a high propensity in female patients including paediatric age group. The clinical presentation varies depending on the age of patient, location and size of the cyst. The symptoms are mostly due to mass effects and rarely complications such as malignancy. Being a rare entity, it is generally misdiagnosed. Differential diagnosis mostly includes rectal duplication cyst, sacrococcygeal teratoma and anterior meningocele. Radiological imaging such as computed tomography scan and magnetic resonance imaging is useful in the diagnosis. The treatment of choice is complete excision to prevent recurrence, infection and malignant degeneration. We have reviewed previous literature and given our valuable information regarding the same.